Ethanolic Extract of Allium cepa Stimulates Glucose Transporter Typ 4-Mediated Glucose Uptake by the Activation of Insulin Signaling - Gautam, Sudeep; Pal, Savita; Maurya, Rakesh; Srivastava, Arvind K. (Planta Medica, 2015)
The present work was undertaken to investigate the effects and the molecular mechanism of the standardized ethanolic extract of Allium cepa (onion) on the glucose transport for controlling diabetes mellitus. A. cepa stimulates glucose uptake by the rat skeletal muscle cells (L6 myotubes) in both time- and dose-dependent manners. This effect was shown to be mediated by the increased translocation of glucose transporter typ 4 protein from the cytoplasm to the plasma membrane as well as the synthesis of glucose transporter typ 4 protein. The effect of A. cepa extract on glucose transport was stymied by wortmannin, genistein, and AI½. In vitro phosphorylation analysis revealed that, like insulin, A. cepa extract also enhances the tyrosine phosphorylation of the insulin receptor-β, insulin receptor substrate-1, and the serine phosphorylation of Akt under both basal and insulin-stimulated conditions without affecting the total amount of these proteins. Furthermore, it is also shown that the activation of Akt is indispensable for the A. cepa-induced glucose uptake in L6 myotubes. Taken together, these findings provide ample evidence that the ethanolic extract of A. cepa stimulates glucose transporter typ 4 translocation-mediated glucose uptake by the activation of the phosphatidylinositol-4,5-bisphosphate 3-kinase/Akt dependent pathway.
Keywords: Allium cepa; Amaryllidaceae; Allioideae; L6 myotubes; insulin; glucose uptake